THE CORRELATION BETWEEN STUDENTS' HABIT OF WATCHING ENGLISH MOVIE AND THEIR VOCABULARY MASTERY: A QUANTITATIVE RESEARCH AT THE EIGHTH-GRADE STUDENTS OF SMP K BHARATA 2 JUMAPOLO IN THE 2022/2023 ACADEMIC YEAR - Ayu Sari Dewi; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2023)
This study aims to analyze the form of correlation between students’ habit of watching English movies and their vocabulary mastery at the eighth-grade students of SMP K Bharata 2 Jumapolo in the 2022-2023 academic year. The researcher used the quantitative method. The research gave a questionnaire consisting of 30 items and a vocabulary test to gather the data. The finding of this study indicated that there is a positive correlation between students’ habits of watching English movies and students’ vocabulary mastery. It is proven by the result of the calculation of rxy 0. 549 > rtable in the significant table 5% (0.396) and1% (0.505). Then it could be concluded that the alternative hypothesis (Ha) is therefore deemed to be accepted and the null hypothesis (Ho) is rejected. In this research, it could be concluded that there is a positive correlation of the research between students’ habits of watching English movies and students’ vocabulary mastery. That means the habit of watching English has an impact, the better student vocabulary mastery. Key words: Habit Watching English Movie, Vocabulary Mastery, Correlational Study